In‐Situ Sonication for Enhanced Recovery of Aquifer Microbial Communities. Issue 5 (12th August 2013) - Ugolini, Fabio; Henneberger, Ruth; Bürgmann, Helmut; Zeyer, Josef; Schroth, Martin H.
Abstract Sampling methods for characterization of microbial communities in aquifers should target both suspended and attached microorganisms (biofilms). We investigated the effectiveness and reproducibility of low‐frequency (200 Hz) sonication pulses on improving extraction efficiency and quality of microorganisms from a petroleum‐contaminated aquifer in Studen (Switzerland). Sonication pulses at different power levels (0.65, 0.9, and 1.1 kW) were applied to three different groundwater monitoring wells. Groundwater samples extracted after each pulse were compared with background groundwater samples for cell and adenosine tri‐phosphate concentration. Turbidity values were obtained to assess the release of sediment fines and associated microorganisms. The bacterial community in extracted groundwater samples was analyzed by terminal‐restriction‐fragment‐length polymorphism and compared with communities obtained from background groundwater samples and from sediment cores. Sonication enhanced the extraction efficiency up to 13‐fold, with most of the biomass being associated with the sediment fines extracted with groundwater. Consecutive pulses at constant power were decreasingly effective, while pulses with higher power yielded the best results both in terms of extraction efficiency and quality. Our results indicate that low‐frequency sonication may be a viable and cost‐effective tool to improve the extraction of microorganisms from aquifers, taking advantage of existing groundwater monitoring wells.